If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(t + 5) = 14 Reorder the terms: -7(5 + t) = 14 (5 * -7 + t * -7) = 14 (-35 + -7t) = 14 Solving -35 + -7t = 14 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -7t = 14 + 35 Combine like terms: -35 + 35 = 0 0 + -7t = 14 + 35 -7t = 14 + 35 Combine like terms: 14 + 35 = 49 -7t = 49 Divide each side by '-7'. t = -7 Simplifying t = -7
| 4/5x=2 | | -4x=-18+5x | | (5x^0/10x^-3y^2)^2 | | 12/x=5/9 | | 13w-9w+w=20 | | 5x+4(3-2x)=6 | | 20s-20s+s+s+4s=12 | | 5/9-12/x | | 6a+a=-7 | | 2(2x+3)-7x=18+5(x+3x) | | 14v+4v-18v+v=7 | | 4[5(1)-3]= | | ln*4x^2=21 | | S/Q-T/Q=1 | | 11k+-6k-k=-2 | | x-45/2=25 | | x+y+9z=10 | | 8z-6z=20 | | (x^4)*e(x)-7=0 | | 2d-2d+3d=3 | | (7y+6)-(3+6y)=8 | | 4x(-114+x^2)=0 | | 26x^2+3x-8=0 | | 8(y-3)+2y=18 | | 10=10-2x | | 2d-d+1=13 | | C=3.14/2 | | 0=-16t+46t+6 | | -5x/7=10/3 | | m=45+18m+60+18m | | 2/7x49 | | 20x-16x=20 |